Prognostic significance of B7H4 expression in patients with optimally or maximally cytoreduced ovarian clear cell carcinoma (Annals of Medical Research, 2021)
Aim: Ovarian clear cell carcinoma is known as an aggressive subtype of malignant ovarian neoplasm due to being relatively resistant to platinum based chemotherapy. Therefore, more effective treatment modalities in ovarian clear cell carcinoma are needed. To investigate the association among expression levels of B7H4 with clinicopathological characteristics and also, survival outcomes of patients with ovarian clear cell carcinoma. Material and Methods: Formalin-fixed, paraffin-embedded tissue blocks from 31 patients with histologically proven ovarian clear cell carcinoma were eligible for the study. Tissue blocks were immunohistochemically stained with B7H4 antibody and scored for expression levels of B7H4. The association between expression levels of B7H4 and the clinicopathological characteristics and survival outcomes of patients were evaluated.Results: Maximal and optimal cytoreductive surgery rates were 45.2% and 54.8%, respectively. The 5-year disease-free survival and overall survival rates were 55.6% and 56.6% for the entire cohort, respectively. All tumor specimens had positive immunohistochemical staining with B7H4 antibody to some extent. Of the 31 patients, 14 (45.2%) showed high expression and the remaining had low expression with B7H4. There was no significant difference between expression levels of B7H4 and clinicopathological characteristics of patients. The 5-year disease-free survival rate was 52.9% in the low expression group and 61.2% in the high expression group. The 5-year overall survival rates were comparable between the low expression group and the high expression group (47.2% and 67.5%, p=0.35). Conclusion: IB7H4 expression is a biomarker for ovarian clear cell carcinoma but it is unrelated with clinicopathologic characteristics and survival outcomes of patients.
Keywords: Ovarian clear cell carcinoma; B7H4; immunotherapy; cytoreductive surgery